Caring for Individuals with Chronic Illness and Minor Depression: Latino Perceptions of Caregiver Burden. Issue 1 (2nd January 2017) - Corvin, Jaime; Chan, Isabella; Tezak, Ann; Carpenter, Kelly; Aguado Loi, Claudia; Gonzales, Junius; Hoare, Ismael
ABSTRACT: Informal caregiving can be fundamental to disease management. Yet, the psychosocial, physical, and financial burden experienced by caregivers can be significant. In the US, Latinos experience increasing rates of chronic conditions, the highest uninsured rates in the country, and a growing dependence on informal caregivers. This article explores the impact of caregiving on caregivers of individuals with comorbid chronic disease and depression. Findings highlight the impact of caregiving on financial insecurity, balancing competing demands, increased emotional distress, and community supports. Findings support the inclusion of caregivers in disease management programs to enhance psychosocial outcomes for both caregivers and their patients.